2020
DOI: 10.20517/2394-5079.2020.63
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of coffee in non-alcoholic fatty liver disease: a narrative review

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most common liver diseases and is related to unhealthy lifestyle habits, characterized by a diet rich in sugars and fats leading to excessive calorie intake, and lack of exercise. In recent years, there is a growing incidence of this pathology, raising the attention of hepatologists, endocrinologists, diabetologists, and nutritionists. In this context, the alimentary regimen adopted by patients with NAFLD has become an increasingly scrutinised parameter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…There is a certain negative correlation between coffee consumption and the occurrence and progression of chronic liver diseases, including fatty liver and liver fibrosis. Some epidemiological studies found that the risk of NAFLD in patients who drank coffee was significantly lower than that in patients who did not and a significantly decreased risk of liver fibrosis among NAFLD patients who drank coffee ( Bambha et al, 2015 ; Wijarnpreecha et al, 2017 ; Calabro et al, 2020 ). Vitaglione et alfound that coffee supplementation prevented HFD-induced NAFLD in mice by reducing hepatic fat deposition and modulating pathways of the gut-liver axis and gut microbiota ( Vitaglione et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a certain negative correlation between coffee consumption and the occurrence and progression of chronic liver diseases, including fatty liver and liver fibrosis. Some epidemiological studies found that the risk of NAFLD in patients who drank coffee was significantly lower than that in patients who did not and a significantly decreased risk of liver fibrosis among NAFLD patients who drank coffee ( Bambha et al, 2015 ; Wijarnpreecha et al, 2017 ; Calabro et al, 2020 ). Vitaglione et alfound that coffee supplementation prevented HFD-induced NAFLD in mice by reducing hepatic fat deposition and modulating pathways of the gut-liver axis and gut microbiota ( Vitaglione et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coffee and its bioactive compounds were widely investigated [ 152 , 153 ]. The in vitro study showed that caffeic acid could ameliorate hepatic steatosis and decrease endoplasmic reticulum stress by increasing autophagy in AML12 cells [ 121 ].…”
Section: Mechanisms Of Plant-based Foods and Their Bioactive Compomentioning
confidence: 99%
“…Collectively, green tea and its bioactive compounds (like EGCG) could alleviate AFLD by improving ethanol metabolism, lipid metabolism, oxidative stress, inflammation, and necrosis (Table 1), with increasing the activities of ADH and ALDH and the phosphorylation of ACC, reducing the Coffee and its bioactive compounds were widely investigated [152,153]. The in vitro study showed that caffeic acid could ameliorate hepatic steatosis and decrease endoplasmic reticulum stress by increasing autophagy in AML12 cells [121].…”
Section: Mechanisms Of Teas and Their Bioactive Compounds On Afldmentioning
confidence: 99%
“…Meta-analyses have reported a prevalence ranging between 25 and 32% ( Younossi et al, 2016 ; Park et al, 2021 ). The incidence of NAFLD has tended to increase over time due to behavioral changes leading to unhealthy lifestyles in the global population ( European Association for the Study of the Liver, European Association for the Study of Diabetes, European Association for the Study of Obesity, 2016 ; Li et al, 2019 ; Calabrò et al, 2020 ). The latest meta-analyses showed that the incidence of NAFLD was approximately 42.8–50.9 per 1,000 person-years ( Li et al, 2019 ; Park et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral modification, weight reduction, and drug therapies are hoped to be effective treatments for NAFLD. Despite the fact that there is no approved pharmacological treatment for NAFLD and non-biopsy-proven patients ( European Association for the Study of the Liver, European Association for the Study of Diabetes, European Association for the Study of Obesity, 2016 ; Chalasani et al, 2018 ; Leoni et al, 2018 ), behavioral changes that lead to weight reduction, fat- and carbohydrate-diet adjustment, exercise, proper sleep, and coffee consumption have caught the attention of researchers ( European Association for the Study of the Liver, European Association for the Study of Diabetes, European Association for the Study of Obesity ; Chalasani et al, 2018 ; Leoni et al, 2018 ; Calabrò et al, 2020 ). Numerous studies have shown that coffee consumption has many positive effects on the liver, such as reducing the risk of fatty liver disease, lowering the severity of hepatic steatosis, and slowing the progression of fibrosis ( Molloy et al, 2012 ; Zelber-Sagi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%